Metodologi Tafsir Bi Al-Ra’yi Perspektif Nashr Hamid Abu Zayd - Hidayat, Muhammad Taufiq; Matondang, Husnel Anwar; Muhammad Ziyad Ulhaq (Program Studi Ilmu Al-Quran dan Tafsir, 2024)
This research aims to examine the methodology of using tafsir bi al ra'yi in detail, where most people only discuss the theory of tafsir bi al ra'yi. The methodology used in this research is qualitative with a library research type of research. The research that serves as a comparison to this research is a journal by Muhammad Shabrun Algifari with the title